The Influences of Return on Asset, Return on Equity, Net Profit Margin, Debt Equity Ratio and Current Ratio Toward Stock Price - Ery Yanto; Irene Christy; Pandu Adi Cakranegara (Publisher Cv. Inara, 2021)
This research aims to determine the influences of Return on Asset, Return on Equity, Net Profit Margin, Debt Equity Ratio and Current Ratio toward stock price. The population in this research are all manufacturing companies listed in Indonesia Stock Exchange (IDX). The technique of determining the sample using purposive sampling method and sample acquired three companies from 35 companies from 2016 to 2018. This research contains six variables which are one dependent variable and five independent variables.